Determinación de la huella de carbono para bloques de balsa de madera en la empresa Gibago Cía. Ltda., Distrito Metropolitano de Quito. - Chamorro Avilés, César Eduardo (2015)
The following research work, allowed to determine the carbon footprint product of GIBAGO CÍA LTDA., whose value was 42795 tons of carbon dioxide equivalent per block of balsa for the year 2013. Was applied the GHG Protocol as methodology which establishes three scopes, for determination of tons of carbon dioxide equivalent of product. The first relates scope to the use of fuels, the second scope considered the use of electricity and the third scope is related to the purchase and use of inputs, by liquid discharges and decomposition of organic solid wasted. It´s important develop the base line of the Industry for determinate the direct influence area, whose result was 1168.02 m2, where clearly develops activities for the elaboration of block of balsa. An interview was undertaken, with the general manager of Gibago Cia Ltda., for learn the productive process of the industry, and also was verified inventory of all invoices of the year 2013 and was used the software SimaPro 7,3 to quantify data and generate results of consumption embodied in tons of carbon equivalent to determinate the footprint carbon of product. Finally for control alterative control to ensure won’t generate less greenhouse gases Gibago Cía. Ltda.